The Prolific Partition : Architecture as catalyst for nature reserve conservation structured in the in-between of Urban and Nature - Vosloo, Pieter Tobias (University of Pretoria, 2018)
Mini Dissertation (MArch(Prof))--University of Pretoria, 2018.